Identification and Characterization of an O-Succinyl-L-Homoserine Sulfhydrylase From Thioalkalivibrio sulfidiphilus - Zhu, Wen-Yuan; Niu, Kun; Liu, Peng; Fan, Yu-Hang; Liu, Zhi-Qiang; Zheng, Yu-Guo (Frontiers in Chemistry, 2021)
L-methionine is an important natural amino acid with broad application prospects. A novel gene encoding the enzyme with the ability to catalyze O-succinyl-L-homoserine (OSH) to L-methionine was screened and characterized. The recombinant O-succinyl-L-homoserine sulfhydrylase from Thioalkalivibrio sulfidiphilus (tsOSHS) exhibited maximum activity at 35 ℃ and pH 6.5. OSHS displayed an excellent thermostability with a half-life of 21.72 h at 30 ℃. Furthermore, the activity of OSHS increased 115% after Fe2+ added. L-methionine was obtained with a total yield reached 42.63 g/L under the concentration of O-succinyl-L-homoserine 400 mM (87.6 g/L). These results indicated that OSHS is a potential candidate for applying in the large-scale bioproduction of L-methionine.